We believe in your conspiracy if we distrust you: the role of intergroup distrust in structuring the effect of Islamic identification, competitive victimhood, and group incompatibility on belief in a conspiracy theory. (9th December 2014) - Mashuri, Ali; Zaduqisti, Esti
Abstract : This study examined how distrust towards an out-group believed to be an actor of a conspiracy theory moderates the role of Islamic identification, group incompatibility and competitive victimhood in explaining belief in said conspiracy. The contextual background we used to verify this idea is the belief in a conspiracy theory among Indonesian Muslims about the involvement of Western countries behind terrorism in Indonesia. More precisely, we found only among Muslim participants with high distrust towards Western people that Islamic identification and group incompatibility positively predicted the perception that Muslims, more than other religious groups, are the victim of the Western people and the belief in a theory that these people have conspired to create terrorism in Indonesia. We also hypothesized and found that competitive victimhood significantly mediated the effects of Islamic identification and group incompatibility on the belief in a conspiracy theory. However, in line with the prediction, these mediation roles of victimhood were obtained only among participants with high distrust. We discussed these findings with reference to theoretical and practical implications.